Hybrid ultrasound and single wavelength optoacoustic imaging reveals muscle degeneration in peripheral artery disease - Träger, Anna P.; Günther, Josefine; Raming, Roman; Paulus, Lars-Philip; Lang, Werner; Meyer, Alexander; Kempf, Julius; Caranovic, Milenko; Li, Yi; Wagner, Alexandra; Tan, Lina; Danko, Vera; et al. (Photoacoustics, 2024)
Peripheral arterial disease (PAD) leads to chronic vascular occlusion and results in end organ damage in critically perfused limbs. There are currently no clinical methods available to determine the muscular damage induced by chronic mal-perfusion. This monocentric prospective cross-sectional study investigated n = 193 adults, healthy to severe PAD, in order to quantify the degree of calf muscle degeneration caused by PAD using a non-invasive hybrid ultrasound and single wavelength optoacoustic imaging (US/SWL-OAI) approach. While US provides morphologic information, SWL-OAI visualizes the absorption of pulsed laser light and the resulting sound waves from molecules undergoing thermoelastic expansion. US/SWL-OAI was compared to multispectral data, clinical disease severity, angiographic findings, phantom experiments, and histological examinations from calf muscle biopsies. We were able to show that synergistic use of US/SWL-OAI is most likely to map clinical degeneration of the muscle and progressive PAD.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Muscle degeneration; Muscle imaging; Optoacoustics; Peripheral artery disease; Photoacoustics

Influence of Eversion Endarterectomy and Patch Reconstruction on Postoperative Blood Pressure After Carotid Surgery - Meyer, Alexander; Gall, Christine; Verdenhalven, Julia; Lang, Werner; Almási-Sperling, Veronika; Behrendt, Christian Alexander; Günther, Josefine; Rother, Ulrich (Annals of Vascular Surgery, 2022)
Background: Post carotid blood pressure fluctuation and hypertension (PEH) are associated with increased risk for adverse outcome; there is limited evidence on the impact of eversion endarterectomy (E-CEA) versus conventional endarterectomy with patch closure (C-CEA) on postoperative blood pressure course. Patients and Methods: In this retrospective observational study, 859 consecutive carotid endarterectomy procedures between 2004 and 2014 (C-CEA n = 585 vs. E-CEA n = 274), were evaluated. Pre- and postoperative blood pressure values were recorded from recovery room until third postoperative day and compared between both techniques; influences on the dichotomous target variable “at least one postoperative blood pressure peak”, that is need for postoperative vasodilators, were analyzed by a logistic regression model. Influences on postoperative systolic blood pressure were evaluated by a linear mixed effects regression model. Results: Preoperative baseline blood pressure was not different between both comparison groups. During postoperative course, significantly increased mean systolic blood pressure values in the E-CEA group from recovery room to second postoperative day (recovery room C-CEA: 129.2 mm Hg vs. E-CEA: 136.5 mm Hg; P < 0.001; first postoperative day C-CEA: 132.4 mm Hg vs. E-CEA: 139.3 mm Hg; P = 0.0002; second postoperative day C-CEA: 138.6 mm Hg vs. E-CEA: 143.1 mm Hg; P = 0.023) were observed. No hyperperfusion syndrome was detected as wells as no difference in postoperative complication rate. Frequency of antihypertensive interventions was also elevated in E-CEA group (C-CEA 22.1 % vs. E-CEA 31.8 %; P = 0.003). E-CEA (OR 1.591, 95% CI [1.146; 2.202]; P = 0.005) and presence of preoperatively elevated systolic readings (OR 1.015, 95%CI [1.006;1.024]; P < 0.001) was also associated with increased need for antihypertensive interventions. Conclusion: E-CEA was associated with significantly elevated postoperative blood pressure, compared to C-CEA. C-CEA was associated with postoperative blood pressure decrease; however, no difference as to neurologic and surgical complications was detected between both surgical techniques in clinical practice.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Blood pressure; Carotid artery disease; Endarterectomy; Postcarotid hypertension

Multispectral optoacoustic tomography of the human intestine – temporal precision and the influence of postprandial gastrointestinal blood flow - Paulus, Lars-Philip; Wagner, Alexandra; Buehler, Adrian; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Günther, Josefine; Rother, Ulrich; Lang, Werner; Hörning, André; et al. (Photoacoustics, 2023)
Multispectral optoacoustic tomography (MSOT) holds great promise as a non-invasive diagnostic tool for inflammatory bowel diseases. Yet, reliability and the impact of physiological processes during fasting and after food intake on optoacoustic signals have not been studied. In the present investigator initiated trial (NCT05160077) the intestines of ten healthy subjects were examined by MSOT at eight timepoints on two days, one fasting and one after food intake. While within-timepoint and within-day reproducibility were good for single wavelength 800 nm and total hemoglobin (ICC 0.722–0.956), between-day reproducibility was inferior (ICC −0.137 to 0.438). However, temporal variability was smaller than variation between individuals (coefficients of variation 8.9%−33.7% vs. 17.0%−48.5%). After food intake and consecutive increased intestinal circulation, indicated by reduced resistance index of simultaneous Doppler ultrasound, optoacoustic signals did not alter significantly. In summary, this study demonstrates high reliability and temporal stability of MSOT for imaging the human intestine during fasting and after food intake.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Gut; Inflammatory bowel disease; Intestinal blood flow; Multispectral optoacoustic imaging; Optoacoustic; Photoacoustic; Postprandial; Reliability; Reproducibility

Outcomes and Fate of the Distal Landing Zone Compared Between Prosthetic and Autologous Grafts After Infrainguinal Graft Occlusions - Rother, Ulrich; Gruber, Marc; Behrendt, Christian-Alexander; Günther, Josefine; Lang, Werner; Meyer, Alexander (JOURNAL OF VASCULAR SURGERY, 2022)
Background: Due to an increasing life expectancy, more and more patients experience the failure of peripheral arterial revascularization. This study aims to investigate patients treated for the failure of infra-inguinal bypass grafts, and to investigate the interaction of different bypass materials [great saphenous vein (GSV) and polytetrafluoroethylene (PTFE)] and the further outcome. Methods: Retrospective single-center analysis of consecutive patients treated for acute or chronic occlusion of infra-inguinal bypasses at a university hospital was conducted. Hospitalizations from 1st January 2010 through 31st December 2019 were included. Perioperative parameters from the index operation including graft material (prosthetic vs. autologous) were assessed. After bypass occlusion, the grade of ischemia, as well as the distal landing zone of the redo bypass compared with the primary bypass was investigated. Results: In this study, 158 (65% men and 35% women with a m mean age of 70.5 years) eligible patients were included (57% vein and 42% prosthetic bypass grafts). After graft occlusion, 47% of the patients presented with symptoms of acute limb-threatening ischemia, 53% with symptoms of chronic leg ischemia. The rate of acute limb-threatening ischemia was significantly higher when prosthetic graft material was used during the index operation (p =0.016). Additionally, in case of reoperation, the landing zone of the redo bypass was significantly more distally located after occlusion of prosthetic bypass graft (p = 0.014). Conclusion: Occlusions of prosthetic bypass grafts were associated with significantly higher rates of acute symptoms compared with vein grafts. Additionally, a shift to a more distal landing zone was recognized after the failure of a prosthetic bypass graft during the redo bypass operatio
CRIS-Team WoS Importer:2022-06-03
Keywords: graft failure; infrainguinal bypass; limb-threatening ischemia; prosthetic graft; vein bypass

Outcomes and Fate of the Distal Landing Zone Compared Between Prosthetic and Autologous Grafts After Infra-Inguinal Graft Occlusions - Rother, Ulrich; Gruber, Marc; Behrendt, Christian-Alexander; Günther, Josefine; Lang, Werner; Meyer, Alexander (Frontiers in Surgery, 2022)
Background: Due to an increasing life expectancy, more and more patients experience the failure of peripheral arterial revascularization. This study aims to investigate patients treated for the failure of infra-inguinal bypass grafts, and to investigate the interaction of different bypass materials [great saphenous vein (GSV) and polytetrafluoroethylene (PTFE)] and the further outcome. Methods: Retrospective single-center analysis of consecutive patients treated for acute or chronic occlusion of infra-inguinal bypasses at a university hospital was conducted. Hospitalizations from 1st January 2010 through 31st December 2019 were included. Perioperative parameters from the index operation including graft material (prosthetic vs. autologous) were assessed. After bypass occlusion, the grade of ischemia, as well as the distal landing zone of the redo bypass compared with the primary bypass was investigated. Results: In this study, 158 (65% men and 35% women with a m mean age of 70.5 years) eligible patients were included (57% vein and 42% prosthetic bypass grafts). After graft occlusion, 47% of the patients presented with symptoms of acute limb-threatening ischemia, 53% with symptoms of chronic leg ischemia. The rate of acute limb-threatening ischemia was significantly higher when prosthetic graft material was used during the index operation (p =0.016). Additionally, in case of reoperation, the landing zone of the redo bypass was significantly more distally located after occlusion of prosthetic bypass graft (p = 0.014) Conclusion: Occlusions of prosthetic bypass grafts were associated with significantly higher rates of acute symptoms compared with vein grafts. Additionally, a shift to a more distal landing zone was recognized after the failure of a prosthetic bypass graft during the redo bypass operation.
CRIS-Team Scopus Importer:2022-03-18
Keywords: graft failure; infrainguinal bypass; limb-threatening ischemia; prosthetic graft; vein bypass

Targeting Muscular Hemoglobin Content for Classification of Peripheral Arterial Disease by Noninvasive Multispectral Optoacoustic Tomography - Günther, Josefine; Knieling, Ferdinand; Träger, Anna P.; Lang, Werner; Meyer, Alexander; Regensburger, Adrian; Wagner, Alexandra; Trollmann, Regina; Wölfle, Joachim; Klett, Daniel; Uter, Wolfgang; Uder, Michael; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2023)
Created from Fastlane, Scopus look-up

The relevance of the "angiosome" concept for treatment of chronic limb-threatening ischemia - Rother, Ulrich; Günther, Josefine; Meyer, Alexander; Lang, Werner; Behrendt, C.; Gortz, H.; Rumenapf, G.; Uhl, C. (Gefässchirurgie, 2020)
Background The angiosome concept as a role model for decision making on revascularization in patients with chronic limb-threatening ischemia and the necessary lower leg revascularization has recently been the subject of controversial discussion in the literature. Methods A narrative literature search was conducted in PubMed (US National Library of Medicine). Results and conclusion There are a large number of retrospective studies showing the different relevance of this concept depending on the selected treatment procedure (open surgery vs. endovascular). Comorbidities also have an influence on the relevance. This article summarizes the current literature on the angiosome-oriented revascularization based on the selected treatment procedure and possible pre-existing comorbidities.
CRIS-Team WoS Importer:2021-01-08